Pengaruh Faktor-faktor yang Mempengaruhi Motivasi Terhadap Kinerja Karyawan (Survey Pada Bank Riau Kepri Cabang Tanjung Balai Karimun) - rahmat, adi (Jurnal Daya Saing, 2016)
Abstract: This research is useful to know the factors that influence the motivation on employee performance. The factors that affect motivation include compensation, direction and control, the establishment of effective working patterns and virtue. The study was conducted at the Bank Riau Riau Branch of Tanjung Balai Karimun with a total staff of 30 people. Summary table of the Model can be seen Adjust the value of R Square shows variable compensation, direction and control, the establishment of effective working patterns and virtue effect on performance of 61.7%, while the rest influenced by variables / factors outside the research. While the R value of 81.2%, which means a very strong contribution value of the variable compensation, direction and control, effective working patterns, and the virtue of the performance. Simultaneous research results showed that a significant difference between the variable compensation, direction and control, effective working patterns, and the virtue of the performance, while partially a significant difference between the variable compensation, and the virtue of the performance Keywords: compensation, direction and control, effective working patterns, kindness and performance